New lichen species from Thailand, new combinations and new additions to the Thai lichen biota - Kalb, Jutarat; Kalb, Klaus (Phytotaxa, 2017)
Several collecting trips by the authors (alone or together) over the last ten years in twenty-one provinces of Thailand afforded new additions to the most recent Thai lichen checklist. These are from seven families with an emphasis on the Graphidaceae reflecting the current interest of the authors. Three species are described as new to science: Glaucotrema palaeoprotocetraricum which differs from G. thailandicum in having larger ascospores and producing protocetraric acid, Platygramme subcalubrosa which differs from P. calubrosa in having non-pruinose labia and discs and smaller, less-septate ascospores and Ramonia minima, which differs from R. kandleri in having smaller ascomata, a lower hymenium and a partly brown to blackish exciple. Constrictolumina leucostoma is a new finding for the Palaeotropics and the genera Pseudotopeliopsis, Ramonia and Sclerophyton are new reports for Thailand. New records of Thai species of Hemithecium are transferred to Allographa and Graphis. This necessitated the following new combinations: Allographa stictilabiata (≡ Graphina stictilabiata), Graphis aphaneomicrospora (≡ Hemithecium aphaneomicrosporum) , G. balaghatensis (≡ Hemithecium balaghatense) and Graphis indica (a new name for Hemithecium norsticticum). Further new combinations include Glaucotrema protocetraricum (≡ Ocellularia protocetrarica) and Traponora varians (≡ Lecidea varians). Acanthothecis consocians, Caloplaca bassiae, Chapsa pulchra, Leucodecton occultum, Phaeographopsis palaeotropica, Platygramme australiensis, P. commutabilis, P. discurrens, Sclerophyton seriale, Psudotopeliopsis longisporum, Traponora macrospora and Trinathotrema stictideum are further new additions to the Thai lichen biota. Working keys are presented to all known species of Phaeographopsis and Trinathotrema and to the Thai species of Platygramme.